The structure and influence of different flying high front kick techniques on the achieved height on the example of taekwon-do athletes - Wasik, J. (Archives of Budo, 2012)
Background and Study Aim: The aim of this paper is to establish biomechanical optimization of the high-flying front kick (in taekwon-do terminology referred to as twimyo nopi ap chagi), which would result in developing a more effective method of executing this particular kick. Material and Methods: The study analysed movements of 14 ITF taekwon-do athletes (age: 16.5 + 0.7 yrs; weight 64.1 + 7.0 kg; height 176.5 cm + 4.6 cm). A system of complex analysis of movement called Smart-D (BTS Spa, Italy) was used for the tests. For the purpose of the experimental part of the study the study participants were asked to adopt the same initial stance (in taekwon-do terminology called Niunja So Palmok Degi Maki) and perform the high-flying front kick in two different techniques - using the traditional technique (scissors) and the natural technique (non-scissors). Results: In case of the natural technique used for executing this kick the COG usually starts from the height of 0.9 m. After 0.5 sec. the COG is lowered by 0.1 m so that the athlete can take off having developed the required velocity. At the maximum height of the flight the COG reaches 1.54 m (having risen by 0.64 m), and this is the moment when the knee extension for kick completion occurs. In the traditional technique the COG is located at 0.9 m at the start and then lowers by 0.1 m. When leaping up at take-off the velocity increases immediately and at the flight maximum the COG reaches 1.46 m. This is also the height when the landing stage starts. The local maximum is marked at the height of 1.40 m, which corresponds to the moment of the knee extension needed to complete the kick. Conclusion: The observation shows that there are four main elements which influence the height achieved by an athlete in his jump and these include the height of the centre of gravity at take-off, the flight height of the COG as well as the height determined by the length of the lower limb and the angle formed between the plane perpendicular to the board and the limb. In the natural technique the athletes managed to raise their COG by an average of 74 mm higher than in the traditional technique (p<0.01).